PELATIHAN OPTIMASI PLATFORM SOSIAL MEDIA SEBAGAI MEDIA PEMASARAN PRODUK UMKM DI DUSUN SUKANEGLA, DESA MEKARSARI - Kadiyono, Anissa; Nugraha, Yus; Surwangi, Lilis; Imam, Muhammad; Ghassani, Fildzah; Angelica, Arwen; Fathia, Raina; Gasman, Muhammad (Universitas Mataram, 2024)
Mekarsari Village, as the object of the Integrative KKN-PPM program, has various potential micro, small, and medium enterprises (SMSE). However, their development is hindered due to the lack of understanding of the business owners regarding product marketing through social media. The external parties are required to encourage the community, so it can enhance their motivation and capabilities in managing SMSE. Because of this phenomenon, the discussions, including with all of the SMSE owners in the Mekarsari Village. Consequently, training about socialization activities and social media training are the most effective solutions to increase community awareness and interest in marketing products. This socialization and service program resulted in a better community to the urgencies of social media and online marketplaces. It even successfully motivated the community to create online stores on marketplaces, enabling them to market products with appropriate descriptions, content, and pricing techniques.